Capture and emission time map to investigate the positive VTH shift in p-GaN power HEMTs. (November 2022) - Modolo, N.; Fregolent, M.; Masin, F.; Benato, A.; Bettini, A.; Buffolo, M.; De Santi, C.; Borga, M.; Posthuma, N.; Bakeroot, B.; Decoutere, S.; Vogrig, D.; et al.
Abstract: In this paper, for the first time the threshold voltage instability of 100 V rated p-GaN power HEMTs is investigated by combined pulsed-IV measurements and capture and emission time (CET) maps, by investigating a remarkable time window of 9 decades, from 1 μs to 1000 s. After a statistical analysis to demonstrate the repeatability of the experimental results, pulsed IV characterization revealed the existence of a non-monotonic ΔV TH shift, as a function of the (positive) gate stress bias. To gain further insight on the positive threshold shift, CET map analysis has been carried out at different temperatures: the results provide relevant insight on the physical properties of the population of traps responsible for the VTH shift, most likely located at the AlGaN/GaN interface. In addition, the related capture and emission time-constant as a function of temperature are investigated, thus allowing to extract the activation energies for the trapping and de-trapping processes, and to propose a model for the trapping mechanisms. Highlights: Power GaN HEMTs Capture and Emission Time Map Threshold voltage Shift DCTS